PAGELARAN SENI BUDAYA ANTAR ETNIS DALAM MEWUJUDKAN MODERASI BERAGAMA - Viona T Matitale; Suryanto; Isabella Jeniva; Muslimah; Jhonathan L Alberto; Susi Arianti; Susi Nurjanah; Enjela R Sinaga; Solafide C Tarigan; Venesa Carolina; Esellina; Aprie; Irma Haliza (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Nusantara Real Work Lecture Program - Religious Moderation (KKN NMB) for Religious Universities in 2023 in Kab. Katingan takes the form of organizing community arts and culture performances for residents of the Malan Island Transmigration Settlement Unit (UPT), Buntut Village, Bali District. Malan Island. The people of UPT Malan Island come from Javanese, Sundanese, Batak, Dayak and Flores ethnic groups who have the potential for regional artistic and cultural diversity, but have not been actively displayed in public performances for a long time. The activity implementation method used Asset Based Community Development (ABCD), namely students identify and look for opportunities for assets owned by the community and then develop and empower them. This method started from an introduction where students approach residents and enter various fields including religion, education and health. Then, identified existing asset opportunities and continue implementing the work program. Every cultural asset owned by the community is developed through cultural arts performances on the eve of the Republic of Indonesia's Independence Day celebration on August 17 2023. This cultural arts performance activity aimed to bring together and develop a sense of tolerance and respect for local cultural diversity to strengthen religious moderation for the community at UPT Malan Island. This cultural parade activity brought together people who had different principles and did not want to join SP-1 and SP-2 UPT Malan Island. People from various tribes feel proud and touched because their cultural arts are displayed and appreciated by other communities in an atmosphere of harmony.